Yerba Mate (Ilex paraguarensis) as Bio-Adsorbent for the Removal of Methylene Blue, Remazol Brilliant Blue and Chromium Hexavalent: Thermodynamic and Kinetic Studies - Mazzeo, Leone; Bavasso, Irene; Bracciale, Maria Paola; Cocchi, Marco; Di Palma, Luca; Piemonte, Vincenzo (Water (Basel), 2020)
Yerba mate (Ilex paraguarensis, YM) was used as biomaterial for the removal of anionic and cationic compounds from wastewater. Chromium hexavalent Cr(VI), Remazol brilliant blue (RBB) and methylene blue (MB) were selected as pollutants. A calcination step was performed after the washing and drying steps to evaluate its effectiveness at increasing the adsorption capacity of the solid. Both YM and calcinated YM (CYM) were characterized by means of scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FT-IR) and Brunauer–Emmett–Teller (BET) analysis. Adsorption batch tests revealed that YM was ineffective for the removal of Cr(VI) and RBB, while good results were obtained for MB (up to 80%) without pH dependency of the adsorption process, and CYM was able to remove Cr(VI) (up to 77%) and RBB (up to 65%) but not MB. The adsorption isotherm of MB on YM at 298 K was obtained experimentally and it is well represented by the Langmuir isotherm. YM’s adsorption capacity for MB was estimated to be 59.6 mg/g. Kinetic batch tests were conducted and the experimental results were fitted with a mathematical model. The low influence of temperature compared to the influence of the YM concentration on the adsorption rate was explained.